Perpetuating Inequality: Barriers and Legal Safeguards for Women in Domestic Violence Situations - Amiruddin, Mochammad Zikni; Zuhriah, Erfaniah; Zarapi, Nur Hamizah (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This article endeavors to conduct a comparative and gender-equality-focused analysis of legal policies safeguarding women facing domestic violence in Indonesia and Malaysia. Employing a normative juridical research approach, the study utilizes legal comparison as its methodological framework. Primary, secondary, and other relevant literature data are employed for a descriptive and analytical analysis. The study reveals that Indonesia addresses gender equality in protecting women through Law Number 23 of 2004, while Malaysia relies on the 1994 Domestic Violence Act (Act 521). These legal frameworks not only prescribe criminal sanctions for domestic violence perpetrators but also encompass provisions for victims' psychological, physical, and social recovery. Despite the existence of legal safeguards in both countries, instances of domestic violence persist. Women, often the primary victims, face barriers in reporting or seeking protection due to ingrained social structures, educational factors, economic disparities, and a prevailing patriarchal culture. This phenomenon underscores persistent gender inequality in society. The article contributes by shedding light on the societal reality of ongoing gender inequality, perpetuating domestic violence against women in Indonesia and Malaysia. It advocates for the revision of legal policies pertaining to the protection of women facing domestic violence, grounded in gender equality, to ensure comprehensive safeguarding within the realms of social structure, education, economics, and socio-cultural factors